An Integrated View of Deubiquitinating Enzymes Involved in Type I Interferon Signaling, Host Defense and Antiviral Activities - Qian, Guanghui; Zhu, Liyan; Li, Gen; Liu, Ying; Zhang, Zimu; Pan, Jian; Lv, Haitao (Frontiers in Immunology, 2021)
Viral infectious diseases have posed a great challenge to human health around the world. Type I interferons (IFN-Is) function as the first line of host defense and thus play critical roles during virus infection by mediating the transcriptional induction of hundreds of genes. Nevertheless, overactive cytokine immune responses also cause autoimmune diseases, which require tight regulation of the innate immune response to achieve a balance between viral clearances without causing excessive immune responses. Recently, emerging studies have uncovered that the ubiquitin system, especially deubiquitinating enzymes (DUBs) plays a critical role in regulating innate immune responses. In this review, we highlight recent advances concerning the diverse mechanisms of human DUBs implicated in IFN-I signaling. These DUBs functioned dynamically to calibrate host defenses against various virus infections by targeting hub proteins in the IFN-I signaling transduction pathway. We also present a future perspective on the roles of DUB-substrate interaction networks in innate antiviral activities, discuss the promises and challenges of DUB-based drug development, and identify the open questions that remain to be clarified. Our review provides a comprehensive description of DUBs, and especially of their differential mechanisms that have evolved in the host to regulate IFN-I-signaling-mediated antiviral responses.